Performance Allowance Module Designer for Work Units of State Ministries/Institutions - Umar Jati; Indah Melati (Jurnal Indonesia Sosial Teknologi, 2024)
Performance allowance is a right for every civil servant which is calculated based on employee performance achievements. Performance allowances are included in employee expenditure which ranks third largest in the State Revenue and Expenditure Budget after capital and goods expenditure. The types and procedures for paying performance allowances are very complex, such as master, follow-up, continuous, shortage, 13th month, and THR performance allowances with different calculation formulas according to the grading order, in addition to the number of work units as many as 9,104 for all State Ministries/Institutions with a total of 967,724 employees, the development of a reliable and adequate information system is needed. The Directorate General of Treasury already has a performance allowance module on the web salary application, but it still needs to be improved and refined so that the process of recording, calculating, testing, and disbursing the process is easy and safe. The application design is not only from the side of the work unit but also from the side of KPPN. The research will use the segregation of duties method to map the separation of functions in terms of making and testing performance allowances, while for application design, Famework for The Application of System Thinking (FAST) will be used, especially for the initial four stages, namely scope definition, problem analysis, requirement analysis, and logical design with various uses of diagrams such as business process diagrams, use case diagrams, Flowchart, Data Flow Diagram, Entity Relationship Diagram is to describe the needs, planning of activities, ease and direction in system development.